KERAGAMAN BOTANIS DAN KAPASlTAS TAMPUNG PADANG PENGGEMBALAAN ALAMI KABUPATEN YAPEN: BOTANICAL VARIERTY AND CARRYING CAPACITY OF NATURAL PASTURE AT YAPEN REGENCY - Muhammad Junaidi; Diana Sawen (Fakultas Peternakan Universitas Papua, 2010)
This study was conducted in several natural pasturing at Yapen regency during approximately 1 month. This study to aim detects botanic variety and carrying capacity of natural pasturing Yapen regency, Papua. Survey used in this study. This study is done to identifies and weight plant found at natural pasturing. At natural pasturing founds 22 species that consist of 7 palatable species (grass = Axonophus compressus, Cyperus kylingia (Kylingia monochepala), Andropogon sp, Eleusine indica, Digitaria pruriens, Cyperus rotundus and legume = Drymaria cordata) and 15 non palatable species (Cycloporus aridus, Menchrocephala bicolor, Psidium guajava, Mimosa pudica, Solanum verbascifolium, Commelinna memfusa, Eupatorium odoratum, Borreria laevis, Hyptis rhomboidea, Achyranthes aspera, Sida rhombifolia, Mengodia sarmentosa, Ageratum conyzoides, Murdania nudiflora, Biden pilosa) . Dominant species based on fresh weight are: non palatable species = 53,666 percent and palatable species = 46,333 percent. Palatable species consist of 43,757 percent grass and 2,575 percent legume. Carrying capacity of natural pasturing only 0,56 animal units a hectare or equal with 0,84 head Bali cattle (body weight about 300 kg) a hectare.